Recent Progress in Stimuli-Responsive Hydrogels Application for Bone Regeneration - Abu Owida, Hamza; Alnaimat, Feras (Advances in polymer technology, 2023)
Bone defects have recently surfaced as an important topic to discuss in orthopedic clinics, and as a result, they have captured the attention of the biomedical community as well as the general public. Because of their unique characteristics, such as high water content, softness, flexibility, and biocompatibility, hydrogels are gaining more and more traction in the field of tissue regeneration research within the medical industry. Intelligent biomaterials, like hydrogels, are much better than their predecessors because they can respond to new stimuli on multiple levels, such as the physical, chemical, and biological. Because they are sensitive to different outside cues, like shape in three dimensions and conditions between solid and liquid phases, they show certain traits. This indicates that they have the capability of developing into a more efficient material in the future, which would make them better suited to facilitate the localized repair of bone lesions. This article takes a look at hydrogels that alter their shape in response to the environment they are in. Some of the topics covered in this article include the classification of these materials, the concepts that underlie their synthesis, and the current state of research in this potentially fruitful field. This research was conducted with the intention of finding novel ways to treat severe bone defects.